Efforts of the Pre-Marital Education Program in Enhancing Family Resilience by the Office of Women’s Empowerment, Child Protection, Population Control, and Family Planning of Surabaya City - Sukma, Della Juana; Jaroah, Siti (Procedia of Social Sciences and Humanities, 2024)
The high divorce rate is generally caused by several factors, including early marriage, economic issues, differences in perspectives, domestic violence, or even gender inequality. To address this, the Surabaya city government requires its citizens to attend premarital education classes as one of the prerequisites for marriage. This study was conducted to determine the effectiveness of premarital education classes organized by the Office of Women's Empowerment, Child Protection, Population Control, and Family Planning (DP3APPKB) in reducing the divorce rate in Surabaya. A qualitative method was used in this study, with observation and interviews with participants and employees as data collection techniques. Based on the data obtained, it can be concluded that the premarital education class program contributes to reducing the divorce rate in Surabaya. This is because the premarital education class program provides four learning materials that can be used to build family resilience